A 39-year high resolution wave hindcast for the Chinese coast: Model validation and wave climate analysis. (1st July 2019) - Shi, Jian; Zheng, Jinhai; Zhang, Chi; Joly, Antoine; Zhang, Wei; Xu, Pengfei; Sui, Titi; Chen, Tian
Abstract: A new wave database has been built over the period of 1979–2017, which can provide wave parameters with high spatial (1 km along Chinese coast) and temporal (1 h) resolutions. Buoy data and satellite altimeter data are used to evaluate the accuracy of the wave hindcasts. Wave climate analysis is the next stage in which the yearly/seasonal maximum, 100-year return period and mean wave characteristics are analyzed. The maximum of the significant wave height (SWH) in summer and autumn are larger than those in the other seasons, while the seasonal mean values in autumn and winter are larger. Severe wave events analysis reveals the maximum values of the 99th percentile SWH (approximate 6 m) are located around Taiwan Island. The average durations for the events during typhoons are 20–30 h with SWH 2–3 m above the 99th percentile SWH. In contrast, the durations are 10–15 h with intensities less than 1 m in winter. For long-term trends, the 99th percentile SWH increases in most part of the Chinese seas, of 0.5–3 cm per year. The changes in times and durations over the past 39 years are not obvious, but the intensity increases approximate 6 cm per year along typhoon tracks. Highlights: A high resolution and long-term (1979–2017) wave database was established. Strong wave seasonality was observed in different parts of Chinese seas. Extreme wave events and long-term trends along Chinese coast were analyzed.